Governo Lula (2003-2010): elementos de continuidade e de ruptura com o neoliberalismo - Leda, Iann Longhini [UNIFESP] (2017)
The Following Research Seeks To Understand The Relation Between The Lula Government (2003-2010) And The Neoliberalism, Highlighting The Elements Of Continuity And Rupture Concerning The Paradigms Brought By The Neo-Liberal Ideas, Notably When It Relates The Question Of The State Reconfiguration, That Would Cease To Be The Promoter Of Economic Growth To Become An Institution Which Main Goal Is Guaranteeing A Good Environment For Financial Investments.